The State of Poznań climate research with particular focus on the air temperature and urban heat island phenomenon - Półrolniczak, Marek; Kolendowicz, Leszek; Majkowska-Juskowiak, Agnieszka (Acta Geographica Lodziensia, 2019)
The article describes the most important results from selected papers concerning the climate of Poznań. The structure of the paper is twofold. The first part presents articles and topics which are based on the data recoded in the Poznań-Ławica airport meteorological station. The second part presents papers where, in addition to data from the airport station, data from the network measurements of municipal stations are also included. This section contains issues concerning the urban heat island, the surface urban heat island, relations between the urban heat island and atmospheric circulation, the characteristics of air temperature and surface temperature according to the Corine Land Cover classification types, as well as information on the creation of a statistical model of air temperature in town according to satellite and in situ data derived from municipal station.